Pengembangan Model Pembelajaran Student Teams Achievement Division (STAD) untuk Menstimulasi Perkembangan Kognitif Anak Usia Dini - Awalunisah, Sita; Amrullah; Setianingsih, Hesti Putri (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2023)
Cognitive abilities of early childhood are very important to be developed as their provision later. At this time, children are easy to stimulate and receive stimulation from the surrounding environment. Therefore the cognitive development of early childhood is very important to be stimulated, one way that can be done to develop early childhood cognitive is to use the STAD cooperative learning model which is expected to help children develop their cognitive. This study uses the Borg & Gall development model. The subjects of this study were 24 people, 12 for limited trials and 12 people for field tests. Data collection techniques used in this study were interviews, quasi-experimental validation and observation. The results of this study indicate that there is an increase in the cognitive development of group B children after being given STAD cooperative learning. This is indicated by the increasing score in each child's cognitive assessment and the results of the SPSS calculation of early childhood cognitive development have Sig <α (0.016 <0.05). From these results it can be seen that the cognitive development of early childhood before the application of the STAD learning model is significantly different from after the application of the STAD type cooperative learning model.